TINJAUAN YURIDIS BUY BACK GUARANTEE SEBAGAI ALTERNATIF TERHADAP PENYELESAIAN DEBITUR BERMASALAH ATAS KREDIT PEMILIKAN RUMAH BERSUBSIDI PADA BANK (STUDI PADA BANK DI SUMATERA UTARA) - TENGKU OCVAN RANDY (jurnal.unprimdn.ac.id, 2022)
One of the risk mitigation instruments which mostly used by banks in providing Subsidized/Sejahtera mortgage facilities is the Guarantee Agreement. The Guarantee Agreement is commonly known as the Buy Back Guarantee Agreement or the Guarantee Agreement to Buy Back. This agreement is not only contained in Cooperation Agreement clause between bank and developer, it is also stated in the form of a deed in the form of a Buy Back Guarantee Agreement or a guarantee deed to buy back the object of the house collateral by guarantor or insurer. Buy Back Guarantee agreement as an alternative for loan guarantees, namely the provision of guarantees and transfer of right to developers to buy back home guarantees from debtors who experience non-performing loan with the condition of the Land Title Certificates not being complete or solving certificates on process, the legal correlation between developer and debtor is still in the form of a Sale Binding Agreement and/or Mortgage Certificate has not yet been issued. However, in practice, the implementation of the Buy Back Guarantee still encounters many obstacles, either form developer, debtor, and bank side. The research employs normative juridical method, namely the method which is based on applicable legal norms sourced from secondary data consisting of primary, secondary, and tertiary legal materials. Aside of that, to complete the research, the author collect the data from interview of related sources, such as the Banking/Creditor, the Subsidized Housing Developer, and the Notary/Land Deed Maker (PPAT). From the research results it is found that the legal force of the Buy Back Guarantee Agreement as an alternative for non-performing loan settlement in KPR Sejahtera financing does not have executive power as the guarantee deeds that have been regulated and used at guarantee institution. The implementation/execution of the Buy Back Guarantee by the developer in accordance with the agreed agreement must be carried out since the developer receives a notification/request letter from the bank, but in practice, developer almost never carry out buy back on the house collateral directly. The obstacle in implementing the Buy Back Guarantee Agreement in KPR Sejahtera financing are from the developers, debtors, and banks themselves.